Exploring the potent inhibitors and binding modes of phospholipase A2 through in silico investigation. Issue 14 (21st September 2020) - Mahmud, Shafi; Parves, Md. Rimon; Riza, Yasir Mohamed; Sujon, Khaled Mahmud; Ray, Suvendu; Tithi, Fahmida Alam; Zaoti, Zannati Ferdous; Alam, Sanjida; Absar, N.
Abstract: Snake venom of Naja naja comprises of several types of enzymes, and among them, water-soluble proteolytic enzyme, phospholipase A2 (PLA2 ), is noteworthy for its numerous adverse effects, such as cytotoxicity, cardiotoxicity, hemolytic, anti-coagulant, and hypotensive effects, including being highly potent as a neurotoxin. Limited anti-venom therapy (with their lower efficacy) has attracted considerable pharmacological interest to develop potent inhibitors of PLA2 . Thus, 34 experimentally proven and diverse synthetic inhibitors of PLA2 were screened primarily on the basis of Glide extra precision docking and MM-GBSA rescoring function. Then, ten potential hits were subjected to induced fit docking, in which top three potential inhibitors were considered, and those were found to interact with Ca 2+, disulfide binding site, and phosphatidylcholine activation sites, thereby, possibly disrupting the catalytic activity of Ca 2+ as well as the inflammatory functions of PLA2 . These compounds showed positive remarks on various physiochemical properties and pharmacologically relevant descriptors. Gap energy and thermodynamic properties were investigated by employing density functional theory for all compounds to understand their chemical reactivity and thermodynamic stability. Molecular dynamics simulation was performed for 100 ns in order to evaluate the stability and binding modes of docked complexes, and the energy of binding was calculated through MM-PBSA analysis. On the whole, the proposed compounds could be used for targeted inhibition. Communicated by Ramaswamy H. Sarma